2018
DOI: 10.1186/s13690-018-0281-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual and household risk factors of severe acute malnutrition among under-five children in Mao, Chad: a matched case-control study

Abstract: BackgroundSevere acute malnutrition (SAM) is one of the leading causes of morbidity and mortality in Chad. The reasons behind persistently high prevalence of SAM in the Kanem region are still poorly understood, leaving national and international partners without clearly identified drivers to address. Current knowledge of SAM determinants in this context is largely based on very limited data. The aim of this study was thus to investigate individual and household-level risk factors for SAM among under-five child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 21 publications
13
33
0
2
Order By: Relevance
“…The finding was in agreement with studies conducted in India [25], Nigeria [53] and Ethiopia [36]. Food insecurity can be linked to inadequate intake of diversified foods and studies have reported consumption of low dietary diversity food as being associated with acute malnutrition [54,55]. Other studies pointed to the role of low socioeconomic status or monthly income in food insecurity [56][57][58][59] which directly or indirectly reduces the HH purchasing power, and thus, reduces access to food.…”
Section: Discussionsupporting
confidence: 90%
“…The finding was in agreement with studies conducted in India [25], Nigeria [53] and Ethiopia [36]. Food insecurity can be linked to inadequate intake of diversified foods and studies have reported consumption of low dietary diversity food as being associated with acute malnutrition [54,55]. Other studies pointed to the role of low socioeconomic status or monthly income in food insecurity [56][57][58][59] which directly or indirectly reduces the HH purchasing power, and thus, reduces access to food.…”
Section: Discussionsupporting
confidence: 90%
“…Unsurprisingly, the odds of acute malnutrition among children in food insecure HHs were higher than in food secure HHs. The finding was in agreement with studies conducted in India (62), Nigeria (63), and Ethiopia (56) Acute malnutrition in food insecure HHs can also be linked to inadequate intake of diversified foods as studies have reported that consumption of low dietary diversity food (≤ 3 food groups) as being associated with acute malnutrition (64)(65)(66). Other studies also pointed to the role of low socioeconomic status or monthly income in food insecurity (49,66) which directly or indirectly reduces the HH purchasing power, and thus, reduces access to food.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 90%
“…Odds of acute malnutrition were higher among children whose mothers had practiced hand washing only after one or two of the key points compared to those who washed hands more frequently. The World Health Organization (WHO) recommends washing hands at four key time points : before eating, before preparing food, after defecation, and after disposal of child feces (67)., Our finding are similar to other studies where caregivers who washed hands regularly were less likely to have acutely malnourished children (46,52,65). Hand washing reduces the risk of contamination by excreta and thereby transmission of pathogens (68).One of the strength of this study is that this is the first cross-sectional study employing a comparative (control) group Manuscript to be reviewed…”
Section: Manuscript To Be Reviewedsupporting
confidence: 87%
“…Poor nutrition has detrimental effects on children's health, as well as on their physical, mental and social development (2)(3)(4). Consequences of undernutrition can include weakened immunity, susceptibility to long-term developmental delays or deficits, and increased risk of death, as well as prolonged negative effects on learning and economic performance (5)(6)(7). Undernutrition can result from illness, food shortage, inappropriate childcare or feeding practices, or a combination of these factors (5).…”
Section: Introductionmentioning
confidence: 99%
“…Consequences of undernutrition can include weakened immunity, susceptibility to long-term developmental delays or deficits, and increased risk of death, as well as prolonged negative effects on learning and economic performance (5)(6)(7). Undernutrition can result from illness, food shortage, inappropriate childcare or feeding practices, or a combination of these factors (5). Different causes of hunger may therefore be associated with different risk profiles.…”
Section: Introductionmentioning
confidence: 99%